Qing-Xin-Jie-Yu Granules in addition to conventional treatment for patients with stable coronary artery disease (QUEST Trial): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Li, Shengyao; Guo, Ming; Mao, Huimin; Gao, Zhuye; Xu, Hao; Shi, Dazhuo
Abstract Background Recurrent cardiovascular event remains high in stable coronary artery disease (SCAD), especially in patients with multiple risk factors, despite a high rate of use conventional treatment. Traditional Chinese Medicine (TCM) is a promising complementary and alternative medicine for treating SCAD, while evidence for its effect on long-term survival is limited. This study was designed to test if Chinese herbal medicine in addition to conventional treatment is more effective than conventional treatment alone in reducing major adverse cardiac event (MACE) for SCAD patients with multiple risk factors during a 1-year follow-up. Methods This is a multicenter, placebo-controlled, double-blinded, randomized controlled clinical trial. A total of 1500 patients are randomized in a 1:1 ratio to receive the Qing-Xin-Jie-Yu Granules (QXJYG) or the placebo granules, twice daily for 6 months. The primary outcome is the combined outcomes including cardiac death, nonfatal myocardial infarction and revascularization. The secondary outcome is the combined outcomes including all-cause mortality, re-admission for acute coronary syndrome (ACS), heart failure, malignant supraventricular and ventricular arrhythmia influencing hemodynamics, ischemic stroke, and other thromboembolic events during 1-year follow-up. The assessment is performed at baseline (before randomization), 1, 3, 6, 9, and 12 months after randomization. Discussion This is the first multicenter trial sponsored by the national funding of China to evaluate TCM in combination with conventional treatment on 1-year survival in high-risk SCAD patients. If successful, it will provide an evidence-based complementary therapeutic approach for reducing MACE from SCAD. Trial registration The trial was registered in the Chinese Clinical Trial Registry on December 28, 2013. The registration number isChiCTR-TRC-13004370 .